Grain size effects on high cycle fatigue behaviors of pure aluminum. (May 2023) - Wang, B.B.; An, X.H.; Xue, P.; Liu, F.C.; Ni, D.R.; Xiao, B.L.; Liu, Y.D.; Ma, Z.Y.
Highlights: Ideal model materials with different grain sizes were prepared in pure Al by FSP. A linear relationship was acquired between fatigue strength and grain size. FSP pure Al exhibited excellent microstructure stability during cyclic deformation. Large-scale shear bands and grain growth were inhibited in FSP ultrafine grains. Real grain size effects on high cycle fatigue deformation behaviors were revealed. Abstract: Friction stir processing (FSP) was used to prepare coarse-grained (CG), fine-grained (FG), and ultrafine-grained (UFG) materials to investigate the grain size effects on high cycle fatigue properties. A linear relationship similar to the Hall-Petch relationship was acquired between the fatigue strength and grain size. Excellent grain boundaries stability in FSP UFG material inhibited the formation of large-scale shear bands and grain growth, which contributed to higher fatigue strength exponent and fatigue damage resistance. Compared with other UFG materials, increasing the fraction of high angle grain boundaries can significantly improve the fatigue strength.